2016
DOI: 10.1089/cbr.2015.1964
|View full text |Cite
|
Sign up to set email alerts
|

64Cu-PSMA-617 PET/CT Imaging of Prostate Adenocarcinoma: First In-Human Studies

Abstract: The preliminary results of this study demonstrate the high potential of Cu-PSMA ligand PET/CT imaging in patients with recurrent disease and in the primary staging of selected patients with progressive local disease. The acquired PET images showed an excellent resolution of the detected lesions with very high lesion-to- background contrast. Furthermore, the long half-life ofCu allows distribution of the tracer to clinical PET centers that lack radiochemistry facilities for the preparation of Ga-PSMA ligand (sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
157
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(164 citation statements)
references
References 20 publications
4
157
1
2
Order By: Relevance
“…Clinical studies have increasingly confirmed that PSMA is a valuable target for both the diagnosis and the treatment of prostate cancer (4,5). Radiolabeled urea derivatives, including 18 F-DCFBC (6), 18 F-DCFPyL (7), 68 Ga-PSMA-HBED-CC (8), 99m Tc-MIP-1404 (9), 68 Ga/ 64 Cu-DKFZ-PSMA-617 (10)(11)(12), and 18 F-PSMA-1007 (13,14), have been reported to detect primary and metastatic prostate cancer lesions. PSMA PET imaging improves the detection rates for metastatic lesions in lymph nodes and bone, especially at low prostate-specific antigen levels (14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Clinical studies have increasingly confirmed that PSMA is a valuable target for both the diagnosis and the treatment of prostate cancer (4,5). Radiolabeled urea derivatives, including 18 F-DCFBC (6), 18 F-DCFPyL (7), 68 Ga-PSMA-HBED-CC (8), 99m Tc-MIP-1404 (9), 68 Ga/ 64 Cu-DKFZ-PSMA-617 (10)(11)(12), and 18 F-PSMA-1007 (13,14), have been reported to detect primary and metastatic prostate cancer lesions. PSMA PET imaging improves the detection rates for metastatic lesions in lymph nodes and bone, especially at low prostate-specific antigen levels (14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…It has been shown that 64 Cu is suited in combination with diacetyl‐bis(N(4))‐methylthiosemicarbazone (ATSM) and with various tumor‐targeting peptides . This has been exemplified by the use of the radionuclide with somatostatin analogs and prostate‐specific membrane antigen (PSMA), respectively. As it is believed that the radionuclide would be particularly suited for biomolecules with slow in vivo kinetics and delayed tumor accumulation, it may also be combined with plasma protein‐binding ligands such as recently exemplified with albumin‐binding folate conjugates and PSMA ligands .…”
Section: Introductionmentioning
confidence: 90%
“…The first was 64 Cu for PET imaging in the course of a clinical study. 173 Another study tested whether 44 Sc would be a feasible alternative to 68 Ga as a diagnostic match to 177 Lu-PSMA-617. 174 44 Sc has a fourfold longer half-life than 68 Ga and is also a nuclide suitable for PET imaging.…”
Section: Y 225 Ac)mentioning
confidence: 99%